'30+ AND SINGLE? SHAME ON YOU!': EXPERIENCES OF SOCIAL PRESSURE AMONG UNMARRIED WOMEN IN KAZAKHSTAN - Jeffrey van den Brink (Nazarbayev University School of Sciences and Humanities, 2025)
30+ and Single? Shame on You! Experiences of Social Pressure Among Unmarried Women in Kazakhstan This thesis explores how unmarried women aged 30-48 in Kazakhstan experience and navigate social pressure to marry. It situates these experiences within the context of local cultural norms, simultaneous retraditionalisation and postmodernisation processes, and the enduring legacies of Soviet-era gender policy, with particular attention to how patriarchal norms are sustained and reproduced in everyday life. Based on 15 in-depth interviews with urban women, the study examines how social pressure is applied, who exerts it, and how women internalise, resist, or negotiate these expectations. 30+ и не замужем? Позор! Опыт социального давления среди незамужних женщин в Казахстане Предлагаемое вниманию научное исследование посвящено анализу опыта социального давления, связанного с институтом брака, оказываемого на незамужних женщин в возрасте от 30 до 48 лет, проживающих в Казахстане. Рассмотрение данного феномена осуществляется в контексте и с учётом локальных культурных норм, параллельных процессов ретрадиционализации и постмодернизации, а также устойчивого влияния гендерной политики советского периода. Особое внимание уделяется механизмам воспроизводства патриархальных норм в повседневной жизни. Эмпирической основой исследования послужили 15 подробных интервью с городскими жительницами. На их основе проводится анализ форм и источников социального давления, а также стратегий, посредством которых женщины его интериоризируют, отвергают или переосмысляют. 30+ En nog steeds single? Schaam je! Ervaringen van alleenstaande Kazachstaanse vrouwen met sociale druk Deze scriptie onderzoekt hoe ongehuwde Kazachstaanse vrouwen tussen de 30 en 48 jaar sociale druk om te trouwen ervaren en ermee omgaan. Deze ervaringen worden binnen de bredere context van lokale culturele normen, gelijktijdige processen van retraditionalisering en postmodernisering, en de blijvende invloed van de Sovjetperiode op genderverhoudingen geplaatst. Er gaat in het bijzonder aandacht uit naar de mechanismen waarmee patriarchale en traditionele normen in het dagelijks leven in stand worden gehouden en worden voortgezet. Op basis van vijftien diepte-interviews met lokale inwoonsters uit stedelijk gebied wordt onderzocht hoe sociale druk rond genderrollen wordt uitgeoefend, door wie, en welke copingstrategieën vrouwen hanteren om deze verwachtingen het hoofd te bieden.
Keywords: Patriarchy; Hegemonic Femininity; Unmarried Women; Kazakhstani Women; Social Pressure; Experiences of Social Pressure; Uyat; Shame; Gender Roles; Womanhood; Single women; Central Asia; Kazakhstan; Manifestation of Social Pressure; type of access: embargo